ERNST POTENTIALS ON KERR/CFT CORRESPONDENCE FOR EXTREMAL ROTATING BLACK HOLES - FITRAH ALFIAN RANGGA SAKTI (NIM: 20215055))5, MUHAMMAD
Kerr black holes are strong candidates for the astrophysical black holes. The understanding of the microscopic structure of this black hole is quite interesting to be investigated. The holography principle is one way to study the microscopic part of Kerr black holes. There have been a conjecture that there is a duality between nearhorizon geometry of extremal Kerr black hole and the conformal field theory (CFT) on its boundary of the horizon, called by Kerr/CFT correspondence. Here, we review this correspondence where in the background geometry, boundary conditions are found for which the algebra of surface charges enhances the U(1) to one copy of the Virasoro algebra with central charge c = 12J. After finding the conformal temperature, which is T = 1=2(symbol), the entropy is obtained from the Cardy formula that agrees with the Bekenstein-Hawking entropy of the extremal Kerr black hole. In addition, we study the Ernst potentials for extremal Kerr black hole and its magnetized case that are obtained from Ernst equations. Later by stretched horizon formalism, we obtain the transformation to magnetize the central charge of extremal Kerr. Finally, the generalization of the Ernst potentials for extremal Kerr-Newman black hole is shown.